Novel approaches in linkage of data sources to explore the associations between purchase of opioid prescriptions during pregnancy and adverse neonatal outcomes - Nahed O. ElHassan; Corey J. Hayes; Ruchira V. Mahashabde; Xiaotong Han; Chary Akmyradov; Chenghui Li; Teresa Hudson; Robert Mcgehee Jr; Peter M. Mourani; Bradley C. Martin (PLoS ONE, 2026)
Objective To evaluate patterns of opioid purchases by payment source among pregnant women in Arkansas and examine their associations with adverse neonatal outcomes. Methods Liveborn singleton infants born in Arkansas between 2014 and 2016 were identified from the Birth Certificate Records and linked to the All-Payer Claims Database (APCD), capturing public and private insurance claims; the Prescription Drug Monitoring Program (PDMP), recording controlled substance dispensations regardless of payment source; and the Social Determinants of Health Database, providing neighborhood socioeconomic indicators. Pregnancies were categorized as opioid non-buyers or buyers (insurance-only or self-paid). Adjusted odds ratios (AORs) for neonatal outcomes were estimated using Generalized Estimating Equations. Trimester-specific opioid exposure, expressed per 100 morphine milligram equivalents (MME), was analyzed to assess time-related effects. Results This longitudinal retrospective cohort analysis included 27,441 pregnancies; 21% (5,841) involved opioid purchases, with 15% (880) including at least one self-paid transaction. Opioid prescription counts during pregnancy were 3,434 (PDMP), 2,161 (APCD), and 8,579 (both). Compared with non-buyers, opioid buyers had higher adjusted odds of preterm (PT) birth (AOR 1.14, 95% CI 1.02–1.27) and neonatal opioid withdrawal syndrome (NOWS) (AOR 2.10, 95% CI 1.42–3.11), with no significant associations observed for low birth weight, NICU admission, or birth-weight z-score. Increasing MME was associated with higher odds of NOWS in first (AOR 1.0045, 95% CI 1.0011–1.0080), second (AOR 1.0064, 95% CI 1.0025–1.0103), and third (AOR 1.0206, 95% CI 1.0122–1.0291) trimester. No significant differences were found between insurance-only and self-paid buyers for any neonatal outcome. Conclusions Linking APCD and PDMP enabled a comprehensive assessment of prescribed opioid exposure. Opioid purchases were associated with increased risk of NOWS and modestly higher odds of PT birth. The dose and timing of opioid purchase were key determinants of NOWS. Payment source was not associated with differences in neonatal risk.